Hearing Loss and Cognition Among Older Adults in a Han Chinese Cohort - Ren, Fuxin; Luo, Jianfen; Ma, Wen; Xin, Qian; Xu, Lei; Fan, Zhaomin; Ai, Yu; Zhao, Bin; Gao, Fei; Wang, Haibo (Frontiers in Neuroscience, 2019)
Presbycusis (PC) is associated with cognitive decline and incident dementia. Speech reception thresholds (SRT) are used to assess speech detection, which points toward a central component of PC. However, to the best of our knowledge, no previous study has reported the relationship between SRT and cognitive function in older adults in a Han Chinese cohort. Therefore, in this study, we investigate the association of hearing loss, indexed using pure tone average (PTA) and SRT, with cognitive function in a Han Chinese cohort using a standardized neurocognitive battery. Subjects (aged ≥60 years) with no history of psychiatric or neurological diseases were recruited. All subjects underwent a battery of neuropsychological and auditory tests. According to the PTA of the better ear, the subjects were further divided into PC and normal PTA (NP) groups. Regression analyses were performed to examine the relationship between cognitive function and hearing loss in the PC and NP groups and all subjects when controlling for age, sex, education level, diabetes, smoking, and hypertension. Cognitive function was significantly associated with PTA and SRT in all subjects. In all subjects, the correlations between non-verbal cognitive scores and SRT were stronger than those between non-verbal cognitive scores and PTA, whereas the correlations between verbal cognitive scores and PTA were stronger than those between verbal cognitive scores and SRT. Moreover, the correlations between PTA or SRT and cognitive function in the PC group were in principle stronger than those in the NP group. Our findings indicate that cognitive function is significantly associated with PTA and SRT in older adults in a Han Chinese cohort. Therefore, SRT could be an important auditory test for exploring cognitive decline in PC and could complement PTA.